Writing experiences of neurodiverse students in graduate STEM programs - Syharat, Connie Mosher; Hain, Alexandra; Zaghi, Arash E.; Deans, Thomas (Frontiers in Education, 2023)
Background Despite efforts to increase the participation of marginalized students, neurodivergent students remain underrepresented in graduate STEM programs. Prior research shows that these students often experience challenges related to key aspects of writing. The objective of this qualitative study is to deepen understanding of the writing experiences, strengths, and challenges of neurodivergent students pursuing graduate degrees in STEM fields. In this analysis, we consider the factors that influence the writing-specific challenges faced by neurodivergent students in graduate STEM programs. This work also explores how neurodivergent students leverage strengths and strategies for success in graduate-level writing tasks. Results This qualitative study draws on Social Cognitive Theory (SCT) to consider the ways cognitive, behavioral, and environmental factors impact writing experiences. We used thematic analysis of the transcripts from 13 focus groups and 1 interview to examine the writing experiences of 31 students who identify as neurodivergent in graduate STEM programs. The findings suggest that many writing challenges faced by neurodivergent graduate students are behaviors and beliefs that emerge in response to environmental factors such as the culture of STEM fields, prior experiences with writing assignments, anxiety driven by intensive feedback cycles, and perceived and experienced stigma. Study participants employed a range of collaborative and situational strategies to support and enhance their writing productivity. Conclusion These findings may provide insight for current and future neurodivergent graduate students as they adjust to the intense writing demands of graduate degree programs and for graduate program administrators and faculty advisors as they consider new ways to support the academic success of neurodivergent graduate students.